Metohuayo Oil (Caryodendron orinocense Karst) Obtained by Hydraulic Pressing and Expeller: Yield Analysis and Physical-chemical Characteristics - DELGADO SORIANO, VICTOR DANIEL (2022)
The main objective of the research was to obtain metohuayo oil by hydraulic pressing versus screw pressing (at 50, 70 and 90 °C). The variables evaluated on the extracted oil were: extraction yield and physical-chemical. The seed stood out for its high fat content (40.5 %) and color L* (29.3), a* (9.7) and b* (18.4). Screw pressing at 50 °C presented the maximum yield and oil recovery values: 39.2% and 96.9%, respectively. The same trend was observed for the quality parameters analyzed: acidity index, peroxide index, p-anisidine index and coefficients K232 and K268, where their values showed an increase related with temperature levels of the screw pressing. The results showed that the set of physical-chemical characteristics allow the recognition and differentiation of the oils obtained in relation to temperature levels, and through a Principal Component Analysis (PCA) it was possible to infer that this type of results can be used as a recognition tool in this process to distinguish the effect of extraction methods. Finally, the oils obtained by both methods, although they showed statistical differences (p<0.05) in their physical-chemical characteristics, showed values within the ranges established by the Codex Alimentarius. These results propose the extraction of oil by screw pressing as a technological process that improves, compared to hydraulic pressing, the use of metohuayo seed oil produced in the tropical Andes, in accordance with the new market demands.